The “autonomy” of developing countries in the Olympic Movement: Assessing the fate of sports governance transplants in the Global South - García, Borja; Meier, Henk Erik (Frontiers in Sports and Active Living, 2022)
This article introduces the concept of governance transplants to evaluate the impact that being part of the Olympic Movement has on domestic sports governance in Global South developing countries. The article explores the extent to which the IOC is successful in implementing the norms and regulations on sports autonomy as a governance transplant at the national level in countries from the Global South that are part of the Olympic Movement. This is done through a comparative qualitative case study that explores the relations of the IOC, National Olympic Committees, and national governments in Botswana, Guatemala and Sri Lanka. Findings suggest that national structures and legacies have an impact on the way in which the autonomy of sport, as the governance transplant, is translated in those three countries. Although national governments enjoy some agency in ‘translating’ governance transplants, results also suggest that misfits and tensions persist between governmental and sport stakeholders at the national and international level. Such misfits might force the IOC, as a private transnational regulator, to adopt a more pragmatic view on the enforcing of its governance transplants. The results are of relevance to existing discussions on global sports governance and debates as to whether the countries in the Global North might be able to impose their views and their governance transplants if the Global South gets a greater say in transnational sports governance.